In the year 1096 : the first Crusade and the Jews - Chazan, Robert Leon 1936- (Jewish Publ. Soc, 1996)
In 1996 the world commemorates the 900th anniversary of the First Crusade or, more precisely, of the pogroms unleashed by the crusade upon the Jews of the Rhineland. In the Year 1096... presents a clear, highly readable chronicle of the events of 1096. Noted teacher and historian Robert Chazan brings readers to critical moments in Jewish history, illuminating the events themselves, their antecedents, and their far-reaching consequences. Equally important, his book assesses the significance of the events of 1096 within the larger framework of Jewish history, including both the scope of persecution and the record of Jewish resistance. He has created a dramatic portrait of the clash between three conflicting forces in medieval Europe: the German crusaders, the Rhineland burghers, and the Rhineland Jews. His book provides an extensive look at the Christian assaults and the intense Jewish responses, with much material translated directly from remarkable Hebrew narratives which are admirable for both the vividness of their description and the complexity of the portrait they provide. Chazan tells the story of 1096 in "grays," not blacks and whites; that is, he relates stories of Christian enemies, but also of Christian friends, and of Jewish martyrs, but also of Jewish negotiators and converts. The author devotes the second half of In the Year 1096... to tracing these events through the intervening nine centuries of Jewish history. In the second part he surveys the Jewish perception of 1096 over the ages, including both the neglect of these events in some quarters and their emphasis in others; he places 1096 within the lengthy history of anti-Jewish actions and thinking, and examines the unusual behaviors of the Rhineland Jews within the context of historic Jewish responses to persecution.